Efforts to Improve the Quality of Online Learning Through Technology Information at MI Al Islam Balesari Windusari Magelang - Tolkhah; Usman, Nurodin; Mawardi, Imam (Urecol Journal. Part A: Education and Training, 2023)
The research objective is to find out how to improve the quality of online learning for students at MI Al Islam Balesari during the Covid-19 pandemic through information technology. The method used in this study uses qualitative methods with techniques for collecting relevant data information through documents, books, magazines and news. This research uses qualitative methods by producing information in the form of notes and descriptive data contained in the documents studied. In breaking the spread of the Covid-19 virus, the government emphasizes learning activities to be carried out at each home using online learning. information that there are still many factors that hinder educators, MI Al Islam Balesari students and also parents in implementing online learning. With the implementation of online learning that is carried out at home, it creates problems for students and also educators, such as the delivery of learning that is not maximal to be conveyed. In the end, students are given additional assignments, as a result, the tasks that students have become more numerous, this can become a burden for students. educators as well as parents. The implementation of online learning must be improved immediately to improve the quality of education during the Covid-19 pandemic.